Absence of Tropical Cyclone Genesis Over the Western North Pacific in July 2020 and Its Prediction by CFSv2 - Tian, Baoqiang; Fan, Ke (Frontiers in Earth Science, 2021)
There were no TCs generated in July 2020 over the western North Pacific (WNP), which was the first time this had happened during since 1980. This study attempts to understand the cause of there having been no TCs generated in July 2020, and evaluates the prediction skill for the large-scale environmental conditions associated with the TC genesis number (TCGN). Results show that the main causes were the abnormal warming of sea surface temperature (SST) in the North Indian Ocean (NIO) and North Atlantic in July and the abnormal decrease in SST from April and May in the Niño4 region. The NIO SST can affect the large-scale environmental conditions via the SST–precipitation–wind feedback mechanism. Through the interaction between the tropical North Atlantic and the NIO, the abnormally warm North Atlantic SST further strengthened the impact of the NIO SST on the environmental conditions. The monthly difference (MD) of the Niño4 index from April to May is significantly correlated with the TCGN in July. Not only can the Niño4 MD in May affect the environmental conditions by affecting the WNP anticyclone, but it can also affect the NIO SST and precipitation anomalies through a shift in the position of the Walker circulation. Besides, the activity of the MJO also had a certain impact on the absence of TC genesis in July 2020. Although CFSv2 can successfully predict the local feedback affecting the July TCGN, it fails to forecast the large-scale environmental conditions associated with the absence of TC genesis over the WNP in July 2020.